Somatic NLRP3 mosaicism in Muckle-Wells syndrome. A genetic mechanism shared by different phenotypes of cryopyrin-associated periodic syndromes. Issue 3 (10th December 2013) - Nakagawa, Kenji; Gonzalez-Roca, Eva; Souto, Alejandro; Kawai, Toshinao; Umebayashi, Hiroaki; Campistol, Josep María; Cañellas, Jeronima; Takei, Syuji; Kobayashi, Norimoto; Callejas-Rubio, Jose Luis; Ortego-Centeno, Norberto; Ruiz-Ortiz, Estíbaliz; et al.
Abstract : Familial cold autoinflammatory syndrome, Muckle-Wells syndrome (MWS), and chronic, infantile, neurological, cutaneous and articular (CINCA) syndrome are dominantly inherited autoinflammatory diseases associated to gain-of-function NLRP3 mutations and included in the cryopyrin-associated periodic syndromes (CAPS). A variable degree of somatic NLRP3 mosaicism has been detected in ≈35% of patients with CINCA. However, no data are currently available regarding the relevance of this mechanism in other CAPS phenotypes. Objective: To evaluate somatic NLRP3 mosaicism as the disease-causing mechanism in patients with clinical CAPS phenotypes other than CINCA and NLRP3 mutation-negative. Methods: NLRP3 analyses were performed by Sanger sequencing and by massively parallel sequencing. Apoptosis-associated Speck-like protein containing a CARD (ASC)-dependent nuclear factor kappa-light chain-enhancer of activated B cells (NF-κB) activation and transfection-induced THP-1 cell death assays determined the functional consequences of the detected variants. Results: A variable degree (5.5–34.9%) of somatic NLRP3 mosaicism was detected in 12.5% of enrolled patients, all of them with a MWS phenotype. Six different missense variants, three novel (p.D303A, p.K355T and p.L411F), were identified. Bioinformatics and functional analyses confirmed that they were disease-causing, gain-of-function NLRP3 mutations. All patients treated with anti-interleukin1 drugs showed long-lasting positive responses. Conclusions: We herein show somatic NLRP3 mosaicism underlying MWS, probably representing a shared genetic mechanism in CAPS not restricted to CINCA syndrome. The data here described allowed definitive diagnoses of these patients, which had serious implications for gaining access to anti-interleukin 1 treatments under legal indication and for genetic counselling. The detection of somatic mosaicism is difficult when using conventional methods. Potential candidates should benefit from the use of modern genetic tools.